Commit 40728ebe authored by Pavel Kus's avatar Pavel Kus

adding plain substractions to the beginning

parent 329abd33
......@@ -91,7 +91,7 @@
real(kind=C_DATATYPE_KIND) :: w_comb(nq, 4)
real(kind=C_DATATYPE_KIND) :: h_comb(4)
real(kind=C_DATATYPE_KIND) :: h_mat(4, nb-1)
real(kind=C_DATATYPE_KIND) :: h_mat(4, nb)
real(kind=C_DATATYPE_KIND) :: tau1, tau2, tau3, tau4
#endif /* REALCASE==1 */
......@@ -270,10 +270,10 @@
w(1:nq) = w(1:nq) * h1 - ( z(1:nq) * h4 + y(1:nq) * h3 + x(1:nq) * h2)
q(1:nq,1) = q(1:nq,1) - w(1:nq)
q(1:nq,2) = q(1:nq,2) - z(1:nq)
q(1:nq,3) = q(1:nq,3) - y(1:nq)
q(1:nq,4) = q(1:nq,4) - x(1:nq)
! q(1:nq,1) = q(1:nq,1) - w(1:nq)
! q(1:nq,2) = q(1:nq,2) - z(1:nq)
! q(1:nq,3) = q(1:nq,3) - y(1:nq)
! q(1:nq,4) = q(1:nq,4) - x(1:nq)
! h4 = hh(2,4)
! q(1:nq,2) = q(1:nq,2) - (w(1:nq) * h4)
......@@ -307,11 +307,15 @@
! enddo
h_mat(:,:) = 0.0
h_mat(1,4:nb-1) = -hh(2:nb-3, 1)
h_mat(2,3:nb-1) = -hh(2:nb-2, 2)
h_mat(3,2:nb-1) = -hh(2:nb-1, 3)
h_mat(4,1:nb-1) = -hh(2:nb, 4)
q(1:nq, 2:nb) = matmul(w_comb, h_mat) + q(1:nq, 2:nb)
h_mat(1,4) = -1.0
h_mat(2,3) = -1.0
h_mat(3,2) = -1.0
h_mat(4,1) = -1.0
h_mat(1,5:nb) = -hh(2:nb-3, 1)
h_mat(2,4:nb) = -hh(2:nb-2, 2)
h_mat(3,3:nb) = -hh(2:nb-1, 3)
h_mat(4,2:nb) = -hh(2:nb, 4)
q(1:nq, 1:nb) = matmul(w_comb, h_mat) + q(1:nq, 1:nb)
......
Markdown is supported
0% or
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment